2012
DOI: 10.1111/php.12014
|View full text |Cite
|
Sign up to set email alerts
|

The Global Response of Nostoc punctiforme ATCC 29133 to UVA Stress, Assessed in a Temporal DNA Microarray Study

Abstract: Cyanobacteria in nature are exposed not only to the visible spectrum of sunlight but also to its harmful ultraviolet components (UVA and UVB). We used Nostoc punctiforme ATCC 29133 as a model to study the UVA response by analyzing global gene expression patterns using genomic microarrays. UVA exposure resulted in the statistically detectable differential expression of 573 genes of the 6903 that were probed, compared with that of the control cultures. Of those genes, 473 were up-regulated, while only 100 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 55 publications
(70 reference statements)
0
30
1
Order By: Relevance
“…Furthermore, in a genomic microarray study of N. punctiforme exposed to UVA stress, approximately 20 contiguous genes on native Plasmid A were strongly up-regulated throughout the duration of the experiment, 24-96 h of UVA stress. Some of these were up-regulated as high as 90-fold over unstressed cells by 96 h. While most of these genes were of unknown function, two of these genes, Npun_AR040 and Npun_AR048, encode putative VirD4 and VirB4 proteins, respectively [31]. These proteins are part of a typical type IV secretion pathway (T4S) which are generally associated with pilus formation and conjugation, although some have been involved with the formation of sheathed structures [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, in a genomic microarray study of N. punctiforme exposed to UVA stress, approximately 20 contiguous genes on native Plasmid A were strongly up-regulated throughout the duration of the experiment, 24-96 h of UVA stress. Some of these were up-regulated as high as 90-fold over unstressed cells by 96 h. While most of these genes were of unknown function, two of these genes, Npun_AR040 and Npun_AR048, encode putative VirD4 and VirB4 proteins, respectively [31]. These proteins are part of a typical type IV secretion pathway (T4S) which are generally associated with pilus formation and conjugation, although some have been involved with the formation of sheathed structures [6].…”
Section: Discussionmentioning
confidence: 98%
“…For cyanobacteria, which produce oxygen during photosynthesis and contain several UVA-absorbing photosensitizing pigments, UVA can account for much of the damage from solar radiation [13]. In the cyanobacterium Nostoc punctiforme ATCC 29133, for example, acclimation to UVA can potentially involve the differential regulation of 573 genes, or about 8.3 % of all genes in the genome [31].…”
Section: Introductionmentioning
confidence: 99%
“…For organisms such as cyanobacteria that produce oxygen during their metabolic activity and are packed full of UVA-absorbing photosensitizing pigments, UVA can be a very important detrimental factor, and can account for most of the damage to the physiological machinery (Garcia-Pichel, 1998). In the cyanobacterium Nostoc punctiforme ATCC 29133, for example, adaptation to UVA potentially involves the differential regulation of 573 genes, or about 8.3% of all genes in the genome (Soule et al, 2013). In addition to the direct effects of UVR on DNA and proteins, many other cellular processes are also negatively impacted in cyanobacteria (see Castenholz and Garcia-Pichel, 2012 for a review).…”
Section: 1 Biological Effects Of Ultraviolet Radiation On Cyanobacteriamentioning
confidence: 99%
“…Some cyanobacteria possess specific UVA or UVB radiation-sensing photoreceptors that are based on pterin-like chromophores (Moon et al, 2010;Portwich and Garcia-Pichel, 2000). The synthesis of antioxidant proteins is also a common UV radiation shock response (Mittler and Tel-Or, 1991;Shibata, Baba, and Ochiai, 1991;Shirkey et al, 2000;Soule et al, 2013). Additionally, some of the motile, gliding cyanobacteria display behavioral UVR avoidance by vertical migrations (0.4-1 mm) away from the incident UV source in a variety of benthic habitats (Bebout and Garcia-Pichel, 1995;Kruschel and Castenholz, 1998;Nadeau, Howard-Williams, and Castenholz, 1999).…”
Section: Mechanisms Of Uvr Damage Repair and Prevention In Cyanobacteriamentioning
confidence: 99%
“…ROS are generated by the absorption of UVA by endogenous photosensitizers, such as flavoproteins, cytochromes and quinones, and include singlet oxygen, superoxide anions, hydroxyl radicals and H 2 O 2 (Bäumler et al, 2012;Pezzoni et al, 2015). In order to investigate the mechanisms involved in the adaptation of bacteria to UVA, the global transcriptomic response of bacteria exposed to low doses of UVA was analysed in microorganisms such as Shewanella oneidensis, Escherichia coli, Nostoc punctiforme and Enterococcus faecalis (Qiu et al, 2005;Berney et al, 2006a;Soule et al, 2013;Sassoubre et al, 2014). These studies revealed that activation of genes coding for enzymes responsible for ROS detoxification and DNA repair is a common response to UVA exposure.…”
Section: Introductionmentioning
confidence: 99%